If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6d + -5)(4d + -7) = 0 Reorder the terms: (-5 + 6d)(4d + -7) = 0 Reorder the terms: (-5 + 6d)(-7 + 4d) = 0 Multiply (-5 + 6d) * (-7 + 4d) (-5(-7 + 4d) + 6d * (-7 + 4d)) = 0 ((-7 * -5 + 4d * -5) + 6d * (-7 + 4d)) = 0 ((35 + -20d) + 6d * (-7 + 4d)) = 0 (35 + -20d + (-7 * 6d + 4d * 6d)) = 0 (35 + -20d + (-42d + 24d2)) = 0 Combine like terms: -20d + -42d = -62d (35 + -62d + 24d2) = 0 Solving 35 + -62d + 24d2 = 0 Solving for variable 'd'. Factor a trinomial. (5 + -6d)(7 + -4d) = 0Subproblem 1
Set the factor '(5 + -6d)' equal to zero and attempt to solve: Simplifying 5 + -6d = 0 Solving 5 + -6d = 0 Move all terms containing d to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6d = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -6d = 0 + -5 -6d = 0 + -5 Combine like terms: 0 + -5 = -5 -6d = -5 Divide each side by '-6'. d = 0.8333333333 Simplifying d = 0.8333333333Subproblem 2
Set the factor '(7 + -4d)' equal to zero and attempt to solve: Simplifying 7 + -4d = 0 Solving 7 + -4d = 0 Move all terms containing d to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -4d = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4d = 0 + -7 -4d = 0 + -7 Combine like terms: 0 + -7 = -7 -4d = -7 Divide each side by '-4'. d = 1.75 Simplifying d = 1.75Solution
d = {0.8333333333, 1.75}
| 4a+6b=86 | | 32-6x=12-10x | | 5+x=3(x-7)+6 | | 5x+15y=55 | | (4x+1)(6x+3)= | | 5-2x=3+x-4-3x | | 2x+11=-5-2x | | 5q^2-2q=4q^2-4q+15 | | 3(p^2-18p+81)=81 | | -4(x+5)=10 | | 24+8=-2x+10x | | 4(x+7)=23 | | 3x+8-10x=14 | | M^2+8M=3 | | 1150/20.70%= | | 110/70= | | 35=3.50x+7 | | B^2=175 | | 172=12x-5+82 | | Y=3.50(4)+7 | | 8+3-12+6= | | Y=3.50(9)+9 | | 9x^2-12x=-1 | | 3.50x+7=9 | | 2+5n=27 | | 6x+3x=9+12x | | 3z+4=10 | | 6x+3y+2z=44 | | 5(f-2)=5 | | 8(s-7)=-84 | | -(c-4)=2 | | 2(t+4)=0 |